Confiabilidade e reprodutibilidade da autoadministração do teste de caminhada de 6 minutos utilizando app de smartphone discente - Jesus, Matheus Oliveira de [UNIFESP] (2019)
Objective: To evaluate the reliability and reproducibility of self-administration of the 6MWT using a free smartphone APP for step counting. Methods: In the first phase, 83 participants (44 ± 10 years, 27 ± 5 kg/m²) underwent a supervised 6MWT in a 30 m covered runner usinga a triaxial accelerometer and smartphones to compare the total step count (Npac and Npapp). We developed a multiple regression equation to estimate the distance walked on the 6MWT (D6MWT) (R² = 0.609). In the second phase, 25 participants (40 ± 10 years, 27 ± 5 kg/m²) performed the 6MWTsup and two other outdoor 6MWT (D6WMTauto1 and D6MWTauto2) using APP for Npapp counts. Results: Npac was significantly higher than Npapp (mean difference, 58 ± 136 m, p = 0,001). The reliability among these measures was weak (intraclass correlation coefficient (ICC), 0,04: 95% confidence interval (95%CI), -0,52-0,40, coefficient of variation (CV) = 42,9%). The limits of agreement between measures were also not adequate (46%), with mean difference of -8,7%. D6MWTauto2 was not significantly different from D6MWTauto1 (mean difference, 1,94 ± 30,27 m, p = 0,761). The confidence limits were lower 10% with an average difference of 0,2%. The reliability among measurements was also excellent (ICC, 0,91; 0,81-0,96; CV 6,4%). D6MWTauto1 was not significantly different from D6MWTsup (1,68 ± 61 m; p = 0,894) with moderate reliability was not significantly different from D6MWT (ICC, 0,75; 0,42-0,89; CV = 27,5%). Acceptable confidence limits (19%) with significant negative correlation between mena difference and mean values. The difference between D6MWTauto2 and D6MWTsup was not significant (3,64 ± 60,57 m, p = 0,766), good reliability (CCI = 0,79; 0,50-0,91; CV = 6%). Confidence limits lower than 19% with significant negative correlation. Conclusion: The 6MWTauto is valid and presents excellent reliability and reproducibility. Our results suggest that the use of 6MWT in people with higher CAR, when necessary, should be used with caution.